PENGARUH TAYANGAN KEKERASAN DALAM FILM THE DOLL 3 TERHADAP AGRESIVITAS GENERASI Z - Syifa Batrisyia; Nuriyati Samatan; Yudanto Prayitno (JURNAL BADATI, 2024)
Movies with elements of violenve or horror can increase the potential for aggressive behavior to harm other people. To find out whether there is an effect of violence shown in The Dol 3 on the aggressiveness of the generation z, the researcher therefore uses the S-O-R (Stimulus, Organism, Response) theory. This study uses a quantitative method and uses a quesionnaire as an instrument for data collection, where the sampling technique is determined by the Slovin formula with a known population. The population of this research is The Doll 3 moviegoers with atotal of 1.764.077 viewers. The result of the study also showed that there was an effect of showing violence in the film The Doll 3 on theaggresiveness of the generation z, which was 8,8% or it could be said to have a weak influence.